Phytochromes A and B Mediate Light Stabilization of BIN2 to Regulate Brassinosteroid Signaling and Photomorphogenesis in Arabidopsis - Zhao, Jiachen; Yang, Guangqiong; Jiang, Lu; Zhang, Shilong; Miao, Langxi; Xu, Peng; Chen, Huiru; Chen, Li; Mao, Zhilei; Guo, Tongtong; Kou, Shuang; Yang, Hong-Quan; et al. (Frontiers in Plant Science, 2022)
Phytochromes A and B (phyA and phyB) are the far-red and red lights photoreceptors mediating many light responses in Arabidopsis thaliana. Brassinosteroid (BR) is a pivotal phytohormone regulating a variety of plant developmental processes including photomorphogenesis. It is known that phyB interacts with BES1 to inhibit its DNA-binding activity and repress BR signaling. Here, we show that far-red and red lights modulate BR signaling through phyA and phyB regulation of the stability of BIN2, a glycogen synthase kinase 3 (GSK3)-like kinase that phosphorylates BES1/BZR1 to inhibit BR signaling. The BIN2 gain-of-function mutant bin2-1 displays an enhanced photomorphogenic phenotype in both far-red and red lights. phyA-enhanced accumulation of BIN2 promotes the phosphorylation of BES1 in far-red light. BIN2 acts genetically downstream from PHYA to regulate photomorphogenesis under far-red light. Both phyA and phyB interact directly with BIN2, which may promote the interaction of BIN2 with BES1 and induce the phosphorylation of BES1. Our results suggest that far-red and red lights inhibit BR signaling through phyA and phyB stabilization of BIN2 and promotion of BES1 phosphorylation, which defines a new layer of the regulatory mechanism that allows plants to coordinate light and BR signaling pathways to optimize photomorphogenesis.